Interaksi Sosial Anak Tunagrahita Tipe Down Syndrome di SD Negeri 1 Banda Aceh - Sulaiman Sulaiman; Anjar Candrawati; Mela Santi (Pesona Dasar : Jurnal Pendidikan Dasar dan Humaniora, 2022)
Social interaction is a reciprocal relationship that occurs between individuals with individuals, individuals with groups, groups with groups and lasts a lifetime. The formulation of the problem in this study is how the social interaction of mentally retarded children with the down syndrome type. The purpose of the study was to describe the social interactions of children with mental retardation with Down syndrome. The approach used in this research is a qualitative approach. This type of research is descriptive qualitative. The subjects in this study were grade 1a teachers along with their accompanying teachers and a number of grade 1a students. Data collection techniques in this study using observation and interviews. The results of this study indicate that children with mental retardation of the down syndrome type experience obstacles when interacting with classmates and class teachers, because children have limited articulation (vocals). However, the mentally retarded child with the down syndrome type is able to establish social interactions if the child is accompanied by a companion teacher, both in collaboration and communication. The attitude shown by mentally retarded children with the down syndrome type with classmates and teachers is that children behave naturally and classmates always accept and treat mentally retarded children well. From the results of the study, it can be concluded that the process of interaction with children with Down syndrome type sometimes experiences obstacles, but once the child is able to cooperate with classmates and teachers, the child remains under the supervision of the accompanying teacher. Children with mental retardation type Down syndrome also behaves well with classmates.